Campylobacter coli in Organic and Conventional Pig Production in France and Sweden: Prevalence and Antimicrobial Resistance - Kempf, Isabelle; Kerouanton, Annaelle; Bougeard, Stéphanie; Nagard, Bérengère; Rose, Valérie; Mourand, Gwénaëlle; Osterberg, Julia; Denis, Martine; Bengtsson, Björn O. (Frontiers in Microbiology, 2017)
The purpose of the study was to evaluate and compare the prevalence and antimicrobial resistance of Campylobacter coli in conventional and organic pigs from France and Sweden. Fecal or colon samples were collected at farms or at slaughterhouses and cultured for Campylobacter. The minimum inhibitory concentrations of ciprofloxacin, nalidixic acid, streptomycin, tetracycline, erythromycin, and gentamicin were determined by microdilution for a total of 263 French strains from 114 pigs from 50 different farms and 82 Swedish strains from 144 pigs from 54 different farms. Erythromycin resistant isolates were examined for presence of the emerging rRNA methylase erm(B) gene. The study showed that within the colon samples obtained in each country there was no significant difference in prevalence of Campylobacter between pigs in organic and conventional productions [France: conventional: 43/58 (74%); organic: 43/56 (77%) and Sweden: conventional: 24/36 (67%); organic: 20/36 (56%)]. In France, but not in Sweden, significant differences of percentages of resistant isolates were associated with production type (tetracycline, erythromycin) and the number of resistances was significantly higher for isolates from conventional pigs. In Sweden, the number of resistances of fecal isolates was significantly higher compared to colon isolates. The erm(B) gene was not detected in the 87 erythromycin resistant strains tested.